Simplify the Fraction: -3a^(-2) ÷ -6a^(-6) Step-by-Step

Question

Solve the following exercise:

3a26a6= \frac{-3a^{-2}}{-6a^{-6}}=

Video Solution

Solution Steps

00:00 Simplify the following problem
00:03 A minus divided by a minus always equals a plus
00:10 When dividing powers with equal bases
00:13 The power of the result equals the difference between the powers
00:17 We'll apply this formula to our exercise, and subtract the powers
00:25 We'll divide both the numerical fraction and the unknown fraction
00:29 Let's calculate 3 divided by 6
00:43 This is the solution

Step-by-Step Solution

Due to the fact that the numerator and the denominator of the fraction have terms with identical bases, we will begin by applying the law of exponents for the division of terms with identical bases:

bmbn=bmn \frac{b^m}{b^n}=b^{m-n} We apply it to the problem:

3a26a6=12a2(6)=12a2+6=12a4 \frac{-3a^{-2}}{-6a^{-6}}=\frac{1}{2}\cdot a^{-2-(-6)}=\frac{1}{2}\cdot a^{-2+6}=\frac{1}{2}\cdot a^4 In the first step we simplify the numerical part of the fraction. This is a simple and intuitive step as it makes it easier to work with the said fraction.

3a26a6=36a2a6=12a2a6= \frac{-3a^{-2}}{-6a^{-6}}=\frac{-3}{-6}\cdot\frac{a^{-2}}{a^{-6}}=\frac{1}{2}\cdot\frac{a^{-2}}{a^{-6}}=\ldots We then return to the problem and subsequently obtain the following expression:

12a4 \frac{1}{2}\cdot a^4 Therefore, the correct answer is option C.

Answer

12a4 \frac{1}{2}a^4